Trail mix volume two eaudiobook Mistakes can kill you, the nester and the piute, trail to pie town, big medicine.. - L'Amour, Louis (HighBridge Audio, 2002)
More than any writer before or since, Louis L'Amour brought the American West to life. His action-packed stories dealt with eternal themes: honor, deceit, passion, betrayal, loyalty, courage, love. His settings were historically accurate, his prose riveting, and his characters colorful: good guys, bad guys, tough, roughs, sidekicks, and saints. TRAIL MIX II gathers four popular Louis L'Amour stories, performed by Willie Nelson: "Mistakes Can Kill You," "The Nester and the Piute," "Trail to Pie Town," and "Big Medicine."